Characterizing the subjective experience of episodic past, future, and counterfactual thinking in healthy younger and older adults. Issue 12 (December 2016) - De Brigard, Felipe; Giovanello, Kelly S.; Stewart, Gregory W.; Lockrow, Amber W.; O'Brien, Margaret M.; Spreng, R. Nathan
Recent evidence demonstrates remarkable overlap in the neural and cognitive mechanisms underlying episodic memory, episodic future thinking, and episodic counterfactual thinking. However, the extent to which the phenomenological characteristics associated with these mental simulations change as a result of ageing remains largely unexplored. The current study employs adapted versions of the Memory Characteristics Questionnaire and the Autobiographical Interview to compare the phenomenological characteristics associated with both positive and negative episodic past, future, and counterfactual simulations in younger and older adults. Additionally, it explores the influence of perceived likelihood in the experience of such simulations. The results indicate that, across all simulations, older adults generate more external details and report higher ratings of vividness, composition, and intensity than young adults. Conversely, younger adults generate more internal details across all conditions and rated positive and negative likely future events as more likely than did older adults. Additionally, both younger and older adults reported higher ratings for sensory, composition, and intensity factors during episodic memories relative to future and counterfactual thoughts. Finally, for both groups, ratings of spatial coherence and composition were higher for likely counterfactuals than for both unlikely counterfactuals and future simulations. Implications for the psychology of mental simulation and ageing are discussed.